Strategi Meningkatkan Kinerja Guru Melalui Program Guru Penggerak - Nur Sodik; Fitri Oviyanti; Muhammad Win Afghani (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
The Ministry of Education and Culture launched a teacher motivation training program. The program is a leadership training program designed to make teachers a leader in learning. This study aims to analyze the motivating teacher program, analyze the strategy for improving teacher performance through the motivating teacher, analyze the factors affecting the strategy for improving teacher performance through the teacher program movers in Jakabaring District, Palembang City. This study uses a qualitative method. The research was conducted at SMPN 31 Palembang and SMAN South Sumatra. Informants in this study were prospective teachers, principals, and student representatives. Data collection methods are observation, interviews, documentation and triangulation. The results of this study are first, the Motivating Teacher Program is a leadership training program for teachers to become leaders in learning that has an impact on students. The Motivator Program includes Online Training, Workshops, Conferences, and Mentoring for 9 months for prospective teacher educators. Second, the implementation strategy of the teacher driving program starts from planning to prepare modules, real action. After that, prepare the evaluation results by filling out a journal about the children's feelings in participating in the driving teacher program. The influencing factors are the supporting factors for the Motivating Teacher Program including the government, schools and the environment. While the inhibiting factors are student facilities, signals, online schools and internet access.